The Admissibility of Images and Videos on Social Media in Proving Genocide in the Gaza Strip - Al-Atresh, Issam (Journal of Legal Sciences, 2026)
This study aimed to determine the admissibility of images and videos on social media in proving genocide in the Gaza Strip. The researcher used a descriptive-analytical approach, analyzing the provisions of the Rome Statute of the International Criminal Court (ICC) of 1998 and the ICC Rules of Procedure and Evidence of 2002. The study reached several conclusions, most notably that the ICC Prosecutor, before initiating an investigation based on information derived from images and videos, must verify the credibility of that information. Images and videos on social media are considered digital evidence in criminal proceedings before the ICC. The ICC has discretionary power to assess the relevance and admissibility of images and videos on social media, and to determine their evidentiary value as digital evidence. The study recommended several measures, most notably that the Palestinian government establish a digital documentation center where citizens can submit images. And videos containing information about genocide crimes to him